2005
DOI: 10.1249/01.mss.0000149885.82163.9f
|View full text |Cite
|
Sign up to set email alerts
|

Time of Day Influences the Environmental Effects on Muscle Force and Contractility

Abstract: In summary, our data showed that both the warm exposure and the diurnal increase in body temperature influence muscle contractility and consequently muscle strength. However, the improvement in muscle contractility after these two passive warm-ups cannot be combined in order to improve force to a greater level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 18 publications
7
76
0
Order By: Relevance
“…One such factor is body temperature. By raising body temperature in a warm environment, diurnal variation can be reduced or eliminated [65][66][67] . Similarly, a warm environment improves diurnal variation in the morning 68) .…”
Section: Temporal Effectiveness Of Exercise Training and Sportsmentioning
confidence: 99%
“…One such factor is body temperature. By raising body temperature in a warm environment, diurnal variation can be reduced or eliminated [65][66][67] . Similarly, a warm environment improves diurnal variation in the morning 68) .…”
Section: Temporal Effectiveness Of Exercise Training and Sportsmentioning
confidence: 99%
“…The effects of the circadian rhythm and time of day on short-term maximal exercises (≤1 min) involving anaerobic metabolism have been well investigated (Lericollais et al, 2009;Nicolas et al, 2005;Racinais et al, 2005aRacinais et al, , 2005bSouissi et al, 2004Souissi et al, , 2007aSouissi et al, , 2007bSouissi et al, , 2008. During the Wingate test, peak power (P peak ) and mean power (P mean ) fluctuate with time-of-day, with the circadian acrophase (peak) at 17:24 ± 00:36 h and 18:00 ± 01:01 h (mean ± SD), respectively, and an amplitude of 7.6 ± 0.8% and 11.3 ± 1.1% (mean ± SD), respectively (Souissi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the underlying mechanisms of these time-of-day effects are still under discussion. Even if the circadian rhythm in core temperature is not necessarily the cause of the rhythm in muscle performance (Waterhouse et al, 2007), some studies have suggested that the simultaneous increases in central body temperature (assessed by oral or rectal measurements) and muscular power are causally related because the diurnal increase in central temperature may exert a beneficial passive warm-up effect (Bernard et al, 1998;Melhim, 1993;Racinais et al, 2005aRacinais et al, , 2005b. Although the exact mechanisms to explain this relationship are not known, it has been suggested that higher body temperature may enhance metabolic reactions, increase the extensibility of connective tissue, reduce muscle viscosity, and increase conduction velocity of action potentials (Shephard, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It must, however, be noted that their study was not primarily designed to address the effect of time of day. Hence, the acute loadings and biopsy samplings were not scheduled to early morning and late afternoon hours, when diurnal minimum and maximum in neuromuscular performance is typically found, respectively (12,26,32,33,35). Furthermore, early morning and late afternoon hours are also when hormonal signalling is dramatically different (e.g., cortisol to testosterone ratio -for a review see (16)).…”
mentioning
confidence: 99%